Pengaruh Brand Ambassador Iqbaal Ramadhan Terhadap Minat Pelajar Denpasar dalam Menggunakan Aplikasi RUANG - Maheni, I Gusti Ayu; Gelgel, Ni Made Ras Amanda; Suryawati, I Gusti Agung Alit (E-Jurnal Medium; Vol 2 No 2 (2021): Jurnal Ilmu Komunikasi Vol 2 No 2 Tahun 2021, 2022)
RUANG GURU is an online learning application from Indonesia made by Imam Usman and Belva Devara in 2014. Ruangguru developed an online learning system based on technology which offers virtual classroom, online test, learning video subscription, online private tutor and many other contents which are accessed in their application. One of their marketing techniques is by using advertisements. to attract potential users, they use public figures. RUANG GURU has some brand ambassadors to promote them, one of them is Iqbal Ramadhaan. This research aims to analyze the effect of Iqbal Ramadhaan as brand ambassador towards the learning attitude of students in Denpasar in using RUANG GURU application. This research uses quantitative associative methods with AIDA theory. The result shows that Iqbal Ramadhaan did have an effect towards students at the city of Denpasar to use RUANG GURU application but it was not significant